Clinical and Laboratory Profile of Hospitalized Symptomatic COVID-19 Patients: Case Series Study From the First COVID-19 Center in the UAE - Hannawi, Suad; Hannawi, Haifa; Naeem, Kashif Bin; Elemam, Noha Mousaad; Hachim, Mahmood Y.; Hachim, Ibrahim. Y.; Darwish, Abdulla Salah; Al Salmi, Issa (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction COVID-19 is raising with a second wave threatening many countries. Therefore, it is important to understand COVID-19 characteristics across different countries. Methods This is a cross-sectional descriptive study of 525 hospitalized symptomatic COVID-19 patients, from the central federal hospital in Dubai-UAE during period of March-August 2020. Results UAE’s COVID-19 patients were relatively young; mean (SD) of the age 49(15) years, 25% were older than 60 and <1% were younger than 18 years old. Majority were male; 78% were obese; mean (SD) BMI was 29 (6) kg/m2. While the source of contracting COVID-19 was not known in 70% of patients, 6% reported travel to overseas-country and 24% reported contact with another COVID-19 case/s. At least one comorbidity was present in 54% of patients and 45% had none. The most common comorbidities were diabetes (34%) and hypertension (32%). The mean (SD) of symptoms duration was 6 (3) days. The most common symptoms at hospitalization were fever (65%), cough (56%), and SOB (46%). Most of the laboratory values were within normal range, but 35% of patients had lymphopenia, 9% had neutrophilia, 22% had prolong INR, and 60% had high D-dimer. Chest x ray findings of consolidation was present in 64% of patients and CT scan ground glass appearance was present in 67%. Acute cardiac injury occurred in 24%, acute kidney injury in 21%, liver injury in 19%, ARDS in 30%, acidosis in 22% and septic shock in 18%. Consequently, 29% required ICU admission with 20% needed mechanical ventilation. Conclusions The study demonstrated the special profile of COVID-19 in UAE. Patients were young with diabetes and/or hypertension and associated with severe infection as shown by various clinical and laboratory data necessitating ICU admission.